Inclisiran for the Treatment of Cardiovascular Disease: A Short Review on the Emerging Data and Therapeutic Potential - Kosmas CE; Muñoz Estrella A; Skavdis A; Peña Genao E; Martinez I; Guzman E (Dove Medical Press, 2020)
Constantine E Kosmas,1 Alba Muñoz Estrella,2 Andreas Skavdis,3 Edilberto Peña Genao,4 Ian Martinez,5 Eliscer Guzman1 1Department of Medicine, Division of Cardiology, Montefiore Medical Center, Bronx, NY, USA; 2Department of Medicine, Mount Sinai St. Luke’s-West Hospital, New York, NY, USA; 3School of Medicine, University of Athens, Athens, Greece; 4Cardiology Clinic, Cardiology Unlimited, PC, New York, NY, USA; 5Department of Medicine, John H. Stroger, Jr. Hospital of Cook County, Chicago, IL, USACorrespondence: Constantine E Kosmas Tel +1-646-734-7969Email cekosmas1@gmail.comAbstract: Proprotein convertase subtilisin kexin 9 (PCSK-9)-targeting therapy has arisen as a new line for the treatment of hyperlipidemia. Inclisiran is a double-stranded small RNA molecule that works by blocking the transcription of PCSK-9, leading to a reduction of PCSK9 levels in the hepatocytes, resulting in an increased expression of low-density lipoprotein (LDL) receptors in the hepatocyte membrane and, as a consequence, it reduces the circulating levels of LDL cholesterol (LDL-C). Compared to the other LDL-C-lowering medications, such as statins, ezetimibe and PCSK-9 inhibitors, inclisiran proposes an infrequent dosing of twice a year, while simultaneously providing a significant reduction of LDL-C. Its prolonged effect offers an advantage against medication non-compliance, which is one of the main causes for not achieving LDL-C goals with standard therapy. Inclisiran has also proven to have a relatively safe profile with adverse effects occurring in similar frequency as with placebo. This review aims to present and discuss the current clinical and scientific data pertaining to the role of inclisiran in the management of hypercholesterolemia and treatment of cardiovascular disease (CVD).Keywords: proprotein convertase subtilisin kexin 9, PCSK-9, inclisiran, hypercholesterolemia, cardiovascular disease, CVD